The Effects of Activities Enriched with Game Elements in Mathematics Lessons - Selen Galiç; Bahadır Yıldız (Universidad de Málaga, 2023)
Differentiated instruction is a form of teaching. The content, processes, products, or learning environment can be differentiated with respect to students' readiness to learn, interests, and learner profiles. Enrichment, one of the differentiation strategies, can be described as the student's intensive work on any subject or area. Using game elements can also impact students' achievement, mathematics attitude, and motivation. The aim of this study was to investigate the influence of activities enriched with game elements on students' learner profiles in mathematics lessons and their achievement, motivation, and attitudes. This current study used the quantitative quasi-experimental approach with 24 6th-grade students during two weeks. The Learner Profile Scale was used on the students and then mathematics activities with game elements were prepared for experimental group. An Academic Achievement Test and Attitude and Motivation Towards Mathematics Scales were used as data collection tools before and after the implementation of activities enriched with game elements. Mann Whitney U Test is used to analyse the differences between experimental and control group. Wilcoxon Signed Rank Test is used to analysed the difference pre- and post-test both experimental and control group. According the result significant point for students' academic achievement, motivation and attitude is found as .229, .002 and .043 respectively. Effect size is calculated for students' academic achievement, attitudes and motivation as .34, .58 and .58 respectively. As a result of this study, the use of enriching game elements had positive and larger effect on students' motivation, and attitude in mathematics lessons. Although the differences between experimental and control group is not found significantly for the student's achievement, there is a difference between pre- and post-test and the size of effects is calculated as medium. Hence, the educational gamify activities should be design by considering the students' types.